INVESTIGACIONES SOBRE LISOZIMA III EXPERIMENTO DE LISIS DE PROTEUS MORGANI CON ANTISUERO Y LISOZIMAS DE LA SALIVA DE GATO Y DE LA LECHE DE BURRA - HUERTA, LAURA; CASTANEDA AGULLO, M (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1914)
A new method of demonstrating the union of antigen and antibody is described The test is performed by placing mixtures of antigen and antibody at one end of a strip of filter paper and subjecting it to the ascending current of isotonic NaCl soln in a ma
AN ESC NAC CIENC BIOL
Keywords: INVESTIGACIONES, LISOZIMA III, EXPERIMENTO, LISIS DE PROTEUS MORGANI, ANTISUERO, LISOZIMAS, SALIVA DE GATO, LECHE DE BURRA; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; CRECIMIENTO ANIMAL